To stay or not to stay: the role of sense of belonging in the retention of physicians in rural areas. Issue 1 (31st December 2022) - Mandal, Anchaleena; Phillips, Susan
ABSTRACT: Rural communities across the circumpolar region and worldwide perennially suffer from physician shortages despite decades of attempting targeted strategies for recruitment. Particularly in rural Canada, financial incentives have attracted but not retained a medical workforce. Although the importance of social connection or belonging is a long-established source of well-being, such information has not infiltrated the dialogue or action on physician retention in rural areas. A physician's sense of belonging, arising from that emotional need for social connectedness, is built via bilateral active efforts at community engagement, reciprocity, social integration of family and workplace collegiality. Links between rural upbringing, rural training opportunities and subsequent rural practice likely rest upon fostering this sense of belonging. Policymakers and recruiters might consider how to help physicians adapt, "fit in", and consider they have "come home" when they venture off to rural settings. Empowering the community to be involved in the recruitment and retention of rural physicians may also be effective. Perhaps this approach would better address the age-old battle to retain physicians in rural Canada and around the world.